2003
DOI: 10.1046/j.1365-313x.2003.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar cation/H+ exchange, ion homeostasis, and leaf development are altered in a T‐DNA insertional mutant of AtNHX1, the Arabidopsis vacuolar Na+/H+ antiporter

Abstract: SummaryThe function of vacuolar Na /H antiporter(s) in plants has been studied primarily in the context of salinity tolerance. By facilitating the accumulation of Na away from the cytosol, plant cells can avert ion toxicity and also utilize vacuolar Na as osmoticum to maintain turgor. As many genes encoding these antiporters have been cloned from salt-sensitive plants, it is likely that they function in some capacity other than salinity tolerance. The wide expression pattern of Arabidopsis thaliana sodium prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
236
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(245 citation statements)
references
References 36 publications
7
236
0
1
Order By: Relevance
“…In plants, the significant contribution of the NHX1 homologue to salt tolerance is well documented (59,60). Interestingly, blocking a related kinase, Ca 2ϩ -dependent protein kinase, results in increases in [Na ϩ ] cyt in rice cells due to the lack of activation of a likely vacuolar Na ϩ /H ϩ antiporter (3).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, the significant contribution of the NHX1 homologue to salt tolerance is well documented (59,60). Interestingly, blocking a related kinase, Ca 2ϩ -dependent protein kinase, results in increases in [Na ϩ ] cyt in rice cells due to the lack of activation of a likely vacuolar Na ϩ /H ϩ antiporter (3).…”
Section: Discussionmentioning
confidence: 99%
“…Non-selective cation channels (NSCCs) can also mediate Na + fluxes (Zhao et al 2011), although their molecular/genetic characterization is currently unknown. At the tonoplast, Na + sequestration is linked to cation exchangers (CAX and NHX; Zhao et al 2008;Apse et al 2003) and vacuolar channels (SV and FV;Ivashikina and Hedrich 2005;Isayenkov et al 2010). SV channels are also blocked by luminal Na + (Ivashikina and Hedrich 2005).…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
“…However, a specific demonstration in guard cell opening and closing has not been made in any study of which we are aware. At the tonoplast, vacuolar sequestration of Na + has been attributed to the function of Na + /H + exchangers (NHX; Blumwald and Poole 1985;Apse et al 1999Apse et al , 2003 and both slow-vacuolar (SV) (Hedrich and Neher 1987;Schönknecht et al 2002;Ivashikina and Hedrich 2005) and fast-vacuolar (FV) channels (Isayenkov et al 2010). It has further been suggested that members of the cation exchanger (CAX) family could transport Na + (Luo et al 2005; see also Zhao et al 2008), but, again, none of these candidates is a part of current models of guard cell function.…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
“…All plant NHX-type transporters characterized to date can be classified into two groups: class I and class II (Brett et al, 2005;Pardo et al, 2006). Proteins of class I localize to vacuoles and catalyze Na + /H + and K + /H + exchanges in vitro, whereas the endosomal (non-vacuolar) class-II proteins may show a preference for K + over Na + as the substrate (Venema et al, 2002(Venema et al, , 2003Apse et al, 2003;Rodriguez-Rosales et al, 2008). Biochemical studies have established that AtNHX1, a class-I protein, catalyzes both Na + /H + and K + /H + exchange with similar affinity (Venema et al, 2002;Apse et al, 2003;Yamaguchi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%